Correlation of D-xylose with severity and morbidity-related factors of COVID-19 and possible therapeutic use of D-xylose and antibiotics for COVID-19 (2020)
The SARS-Cov-2 pandemic that currently affects the entire world has been shown to be especially dangerous in the elderly (≥65 years) and in smokers, with notably strong comorbidity in patients already suffering from chronic diseases, such as Type 2 diabetes, cancers, chronic respiratory diseases, obesity, and hypertension. Inflammation of the lungs is the main factor leading to respiratory distress in patients with chronic respiratory disease and in patients with severe COVID-19. Several studies have shown that inflammation of the lungs in general and Type 2 diabetes are accompanied by the degradation of glycosaminoglycans (GAGs), especially heparan sulfate (HS). Several studies have also shown the importance of countering the degradation of HS in lung infections and Type 2 diabetes. D-xylose, which is the initiating element for different sulfate GAG chains (especially HS), has shown regeneration properties for GAGs. D-xylose and xylitol have demonstrated antiinflammatory, antiglycemic, antiviral, and antibacterial properties in lung infections, alone or in combination with antibiotics. Considering the existing research on COVID-19 and related to D-xylose/xylitol, this review offers a perspective on why the association between D-xylose and antibiotics may contribute to significantly reducing the duration of treatment of COVID-19 patients and why some anti-inflammatory drugs may increase the severity of COVID-19. A strong correlation with scurvy, based on gender, age, ethnicity, smoking status, and obesity status, is also reviewed. Related to this, the effects of treatment with plants such as Artemisia are also addressed.